The Organization of Digital Platforms Die Organisation digitaler Plattformen - Ametowobla, Dzifa; Kirchner, Stefan (Zeitschrift für Soziologie, 2023)
Digital platforms pervade contemporary societies, but sociology currently lacks a general concept for investigating them. Platforms combine technology and organizational elements in particular ways, but existing concepts consider these combinations in a onesided manner: Business approaches focus on technological features solely in economic relationships, sociological approaches underestimate the relevance of technology for the multiple relationship forms. Extending on the understanding that all digital platforms share a coreperiphery architecture, we develop the concept of platform organization for the many instances where this architecture enables and governs a social order through digital interfaces. Our paper contributes to a necessary debate on general concepts for sociological research that reconcile the role of technology with the social orders brought about by diverse digital platforms.
CRIS-Team Scopus Importer:2025-04-09
Keywords: Digital Technology; Digitalization; Organization; Organizational Forms; Partial Organization; Platforms; Social Order